Current state of neural networks applications in power system monitoring and control - Hassan, L.H.; Moghavvemi, M.; Almurib, H.A.F.; Steinmayer, O. (Elsevier, 2013)
For over two decades Neural Network (NN) has been applied to power system monitoring and control. Conventional controllers suffer from certain limitations which NN as an Artificial Intelligence (AI) technique is able to overcome. Therefore, many researchers prefer to use NN technique in the monitoring and control of power systems. This paper reviews published recently schemes for control and monitoring based on NN. The performance of various NN controllers is compared with one another as well as to the performance of other types of controllers. This review further reveals that the design of a proper NN control can maintain first-swing stability, damp oscillation, ensure voltage stability and the reliable supply of electric power.